Prognostic impact of CD73 expression and its relationship to PD-L1 in patients with radically treated pancreatic cancer - Tahkola K; Ahtiainen M; Kellokumpu I; Mecklin JP; Laukkarinen J; Laakkonen J; Kenessey I; Jalkanen S; Salmi M; Bohm J (SPRINGER, 2025)
Immune suppressing molecule CD73 is overexpressed in various cancers and associated with poor survival. Little is so far known about the predictive value of CD73 in pancreatic ductal adenocarcinoma (PDAC). The purpose of this study was to investigate the prognostic significance of CD73 in PDAC. The study material consisted of 110 radically treated patients for PDAC. Tissue microarray blocks were constructed and stained immunohistochemically using CD73 antibody. Staining intensity and numbers of stained tumour cells, inflammatory cells, stroma, and blood vessels were assessed. High-level CD73 expression in tumour cells was positively associated with PD-L1 expression, perineural invasion, and histopathological grade. CD73 positivity in tumour-infiltrating lymphocytes was significantly associated with lymph node metastasis. Lymphocytic CD73 positivity was also associated with staining positivity in both stroma and vascular structures. In addition, CD73 positivity in vascular structures and stroma were associated with each other. There were no significant associations between CD73 positive tumour cells and CD73 positivity in any other cell types. PD-L1 expression was associated with CD73 staining positivity in stroma (p = 0.007) and also with histopathological grade (p = 0.033) and T class (p = 0.016) of the primary tumour. CD73 positivity in tumour cells was significantly associated with poor disease-specific (p = 0.021) and overall survival (p = 0.016). In multivariate analysis, CD73 positivity in tumour cells was an independent negative prognostic factor together with histopathological grade, TNM stage, and low immune cell score. In conclusion, high CD73 expression in tumour cells is associated with poor survival in PDAC independently of the number of tumour-infiltrating lymphocytes or TNM stage.